Design Of Online Shopping Application Based On Mobile Devices And Android Studio In PT. Midi Utama Indonesia: Design Of Online Shopping Application Based On Mobile Devices And Android Studio In PT. Midi Utama Indonesia - Bakhtiar Rifai; Yesi Ratna Sari; Nanang Nuryadi (Jurnal Mantik, 2020)
Self-service is an alternative place to shop. a special place that can meet the daily shopping needs of consumers. Product Ordering for customers remains a constraint if the distance of the place of residence with a minimarket are far apart, or lazy customers out due to rain. Of the few existing cases, Order and delivery system is still done over the phone. The way they have constraints, such customers do not know the Menu and price list that is in the minimart. This research aims to build the application so that the delivery Order and delivery information becomes quickly, accurately, and can Order the Products online via smartphones. This application was built using the software Android Studio as the manufacturer of the application and its data base for the management of SQLite. This application can help consumers to get information about the Product- markets are offered as well as facilitate consumers in the process of Ordering a Product and can help increase sales for companies.